COMPARATIVE ANALYSIS OF TOTAL HARMONIC DISTORTION IN VSI FED MULTI-LEVEL INVERTERS - Neelshetty K (International Educational Journal of Science and Engineering, 2026)
Conventional two-level inverter fed induction motor drive system possesses significant quantity of harmonics and makes the induction motor to suffer from severe torque and speed fluctuations. The presence of harmonic also causes Electro-Magnetic Interference (EMI) and motor heating. Large sized filters are required to reduce the magnitude of harmonics, which results in higher cost of the drive system. Multilevel inverters are the most promising and economical option for achieving high-quality output power in high voltage and high power motor drive applications. The system’s capacity to handle electricity is increased when the Multilevel inverter structure is used. Higher level of inverters reduces the Total Harmonic Distortion (THD) and overall performance inverter systems.